The Effects of Cultivation Area and Altitude Variation on the Composition of Essential Oil of Laurus nobilis l. Grown in Eastern, Western and Central Karadeniz Region - Bilge Yılmaz; İlhan Deniz (International Journal of Secondary Metabolite)
Laurus nobilis L. is one of the most valuable non-wood forest products on world export market and Turkey. Turkey is the biggest provider country for Laurus nobilis in the world. Therefore, laurel is an important commercial product for our country. In this study, the effects of cultivation area and altitude variation on essential oil content and quantity of laurel leaves were examined which grown in Trabzon, Bartın and Samsun. It was aimed to determine chemical composition of laurel’s leaves grown in Karadeniz region.   Laurus nobilis L. leaves were collected in three different height ranges. These were 0-100 m, 100-300 m, 300-600 m. Leaves were shade-dried and crushed. A device called ‘’Clevenger’’ was used for getting volatile oil and their yields were calculated according to dry weight. The yields of essential oils ranged between 0.91% to 1.66 %. These essential oils were obtained from Bartin (B2) (100-300 m) and Artvin (A1) (0-100 m) respectively. The major components of these essential oils were 1,8- cineole (19.71%-35.63%), α-terpinyl acetate (12.86%-21.24%), sabinene (5.98%-9.40%), α- pinene (3.67%-8.45%) and β- pinene (2.91%-5.87%) were the most abundant volatile compounds in the leaves of bay.